Pembuatan Tepung Labu Kuning (Kajian Penggunaan Suhu dan Lama Pengeringan) - Trian Adimarta; Marisa Nopriyanti; Irianto SP; Defi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Pumpkin (Cucurbita moschata Duch) is a type of vegetable plant and can be used for various types of food, Pumpkin that has been cut has a lower shelf life than in its whole state so it needs to be processed so it is not easily damaged so it needs to be processed into flour so that it can be processed into flour. durable. The purpose of this study was to determine how to make pumpkin flour and to find out the best treatment variations in making pumpkin flour. The research method in making flour uses variations in temperature and different drying times. Parameters to determine the difference from flour include water content, yield, and color. The results showed that the production of pumpkin flour started from cleaning the skin and seeds, washing, weighing, cutting into thin slices, drying, and sifting. The results of the analysis of the water content of 40oC treatment for 48 hours is 19.92%, 50oC treatment for 36 hours is 11.63%, and 60oC treatment for 24 hours is 10.36%, pumpkin flour yield is 51.56%, 17, 71%, and 14.63%, while the color analysis of the 40oC treatment was significantly different from the 50oC and 60oC treatment. Of the three treatments, 60oC was the best treatment.